SIMPLE WAYS TO DIFFERENTIATE BETWEEN PERMUTATIONS AND COMBINATIONS IN COMBINATORICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article provides a simple and easy way to differentiate between permutations and combinations, which are rare in textbooks and manuals and difficult to work with.